15 Year Aceh Economic Leverage Analysis Post-Mou Helsinki - Sri Handayani; Ivon Jalil; Aswin Nasution (Britain International for Academic Research (BIAR-Publisher), 2021)
Conflict and regional economic development are two things that are interconnected, including the post-conflict conditions that have occurred. The Aceh conflict which was reconciled through the Helsinki MOU on August 15, 2005, in its course of text and social influence, affected the economic development of Aceh. Research on the analysis of leverage factors for the Acehnese economy 15 years after the peace period shows that the Acehnese economy is still in an unsustainable status with the main lever factor being human development index followed by regional expenditure, per capita expenditure, working population based on main employment, GRDP on the basis of price. Applicable, and agricultural production. Aceh's economic development, apart from requiring supporting infrastructure, really needs to pay attention to the development of its human index.